Interrogation and torture: integrating efficacy with law and morality - Barela, Steven J.; Fallon, Mark; Gaggioli, Gloria; Ohlin, Jens David (Ethics, national security, and the rule of law, 2020)
Foreword / Nils Melzer, UN Special Rapporteur on Torture -- Introduction : Legal, Moral and Effective Interrogation / Steven J. Barela. Jens David Ohlin -- Defining Torture and the Obligation of Systematic Review in the CAT Treaty / Manfred Nowak, Giuliana Monina -- Personality Disruption as Mental Torture : The CIA, Interrogational Abuse, and the U.S. Torture Act / David Luban, Katherine S. Newell -- The Field of Torture Today : Ten Years On from Torture and Democracy / Darius Rejali -- The HIG Project : The Road to Scientific Research on Interrogation / Mark Fallon, Susan E. Brandon -- Developing Rapport and Trust in the Interrogative Context : An Empirically-Supported Alternative / Laure Brimbal, Steven M. Kleinman, Simon Oleszkiewicz, Christian A. Meissner -- Investigative Interviewing : From England to Norway and Beyond / Ray Bull, -- Asbjørn Rachlew -- Interrogating the Brain: Torture and the Neuroscience of Humane Interrogation / Shane O'Mara -- Professional Standards in the Aftermath of Torture : The Struggles of the American Psychological Association / Stephen Soldz, Steven Reisner -- What Can Be Asked of Interrogators? / Michael Skerker -- Beyond Ethics on the Sly : The Behavioral Sciences & National-Security Interrogation / M. Gregg Bloche -- Cycles of Compulsion : Efficacy and Legality in the History of Israeli Torture Debates and Practice / Karin Loevy -- A Qualified Defense of the Obama Administration's Record on Torture / John T. Parry -- Unmasking the Challenges : Interrogation and International Law / Gloria Gaggioli, Pavle Kilibarda -- Torture, Dignity and the Rule of Law / J.M. Bernstein -- Justifying Too Much : Utilitarianism as a Moral Theory / Bob Brecher -- Reclaiming Bentham on Torture / Steven J. Barela -- Preventing Torture : What Works? / Mark Thomson, Barbara Bernath -- Repairing the Damage from Illegal Acts of State : The Costs of Failed Accountability in the U.S. / Claire Finkelstein, Steve Xenakis -- Drinking from a Poisoned Chalice : A Portrait of the U.S. Military Commissions at Guantánamo / John G. Baker, Mary E. Spears, Katherine S. Newell -- Setting Universal Standards for Non-Coercive Interviews and Associated Safeguards / Juan E. Méndez, Andra Nicolescu -- Afterword : The Corrosive Strategic Legacy of Torture / Alberto Mora